2023
DOI: 10.47992/ijcsbe.2581.6942.0304
|View full text |Cite
|
Sign up to set email alerts
|

Advances and New Research Opportunities in Quantum Computing Technology by Integrating it with Other ICCT Underlying Technologies

P. S. Aithal

Abstract: Purpose: To explore the vast potential and possibilities that arise from synergizing quantum computing with other foundational technologies in the field of Information, Communication, and Computing Technologies (ICCT). By integrating quantum computing with other ICCT technologies, such as artificial intelligence, data analytics, cryptography, and communication networks, researchers aim to unlock unprecedented computational power and efficiency, thereby revolutionizing various industries and scientific domains.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(5 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…The integrated approach presented in the present paper, which encompasses fundamental quantum concepts, quantum computing, and quantum cryptography, is echoed in Aithal's work [21]. Notably, Aithal underscores synergies among various topics within the realm of Information, Communication, and Computing Technologies (ICCT).…”
Section: Literature Reviewmentioning
confidence: 87%
“…The integrated approach presented in the present paper, which encompasses fundamental quantum concepts, quantum computing, and quantum cryptography, is echoed in Aithal's work [21]. Notably, Aithal underscores synergies among various topics within the realm of Information, Communication, and Computing Technologies (ICCT).…”
Section: Literature Reviewmentioning
confidence: 87%
“…Moreover, the proliferation of data centers and cloud computing has raised concerns about centralized energy consumption [100][101][102]. However, Aithal [103] and Mishra and Singh [104] showed that ongoing technological innovations and solutions, including energy-efficient hardware and quantum computing, offer potential avenues for mitigating these challenges [105]. Analyzing the situation in EU countries reveals a discernible gap in investigations into the relationship between digitalization and energy consumption for EU countries considering energy consumption, the energy structure, and energy intensity.…”
Section: Relationship Between Digitalization and Energy Consumptionmentioning
confidence: 99%
“…Furthermore, the integration of quantum computing with other Information, Communication, and Computing Technologies (ICCT) is opening new avenues for research and application. Aithal (2023) explores the vast potential that arises from synergizing quantum computing with foundational technologies like artificial intelligence, data analytics, cryptography, and communication networks. This interdisciplinary exploration is aimed at unlocking unprecedented computational power and efficiency, thereby revolutionizing various industries and scientific domains.…”
Section: Selection Criteriamentioning
confidence: 99%